The role of lateral tension in calcium-induced DPPS vesicle rupture - Marr, James M (Langmuir : the ACS journal of surfaces and colloids, 2012)
We assess the role of lateral tension in rupturing anionic dipalmitoylphosphatidyserine (DPPS), neutral dipalmitoylphosphatidylcholine (DPPC), and mixed DPPS-DPPC vesicles. Binding of Ca(2+) is known to have a significant impact on the effective size of DPPS lipids and little effect on the size of DPPC lipids in bilayer structures. In the present work we utilized laser transmission spectroscopy (LTS) to assess the effect of Ca(2+)-induced stress on the stability of the DPPS and DPPC vesicles. The high sensitivity and resolution of LTS has permitted the determination of the size and shape of liposomes in solution. The results indicate a critical size after which DPPS single shell vesicles are no longer stable. Our measurements indicate Ca(2+) promotes bilayer fusion up to a maximum diameter of ca. 320 nm. These observations are consistent with a straightforward free-energy-based model of vesicle rupture involving lateral tension between lipids regulated by the binding of Ca(2+). Our results support a critical role of lateral interactions within lipid bilayers for controlling such processes as the formation of supported bilayer membranes and pore formation in vesicle fusion. Using this free energy model we are able to infer a lower bound for the area dilation modulus for DPPS (252 pN/nm) and demonstrate a substantial free energy increase associated with vesicle rupture